Esophageal mucosal innervation in functional heartburn: Closer to healthy asymptomatic subjects than to non‐erosive reflux disease patients. Issue 9 (21st June 2019) - Nikaki, Kornilia; Woodland, Philip; Lee, Chung; Ghisa, Matteo; Marinelli, Carla; Savarino, Edoardo; Sifrim, Daniel
Abstract: Background: Mucosal innervation in non‐erosive reflux disease (NERD; pathological esophageal acid exposure, normal macroscopic mucosa) is clearly distinct from that of healthy volunteers (HV) and from patients with esophagitis or Barrett's esophagus: The nerves in NERD are situated much closer to the luminal surface of the mucosa. Patients with functional heartburn (FH) have a similar symptom profile to patients with NERD and indistinguishable macroscopic appearances. However, they have physiological acid exposure and no reflux‐symptom association. The aim of our study was to delineate the position of esophageal mucosal nerve fibers in patients with FH and compare it with that in NERD and HV. Methods: Distal esophageal biopsies from patients with FH were immunohistochemically stained for CGRP. CGRP‐positive nerve fibers were identified, and their position relative to the lumen was determined. These results were compared to our previously published cohort of HV and NERD. Results: Eleven patients were included in the FH group with a mean age of 46 years (range 33‐69); 7F:4M. Nine patients had visible nerve fibers. The location of the afferent nerve fibers in the distal esophageal mucosa (median of 22, range 10.4‐28) was similar to the HV group (median 25.5) and significantly deeper than the superficial nerves seen in NERD (median 9.5). Conclusions: The mucosal innervation pattern in FH is more alike that of healthy individuals than that of NERD, with afferent nerves lying deep in the mucosa, away from the luminal surface. This supports the theory that heartburn in FH has a distinct nociceptive pathophysiology. Abstract : The pathogenesis of heartburn in patients with functional heartburn is unknown and distinct to that of non‐erosive reflux disease. The esophageal mucosa afferent nerves are as deep as in healthy individuals.